STOOL ANTIGEN (HPSA) TEST IN DETECTION OF HELICOBACTER PYLORI INFECTION AMONG ADULT DYSPEPTIC PATIENTS IN TRIPOLI, LIBYA - Huwiage, G.M.; Nami, A. A.; Akadh, A. H. (International Journal of Medicine and Medical Research, 2020)
Background. Helicobacter pylori is the most common infection in the world. Relationship between H. pylori and dyspepsia was confirmed by many studies, it has been strongly associated with peptic ulcer disease and gastric cancer. In that respect, several invasive and noninvasive methods for the diagnosis of H. pylori infection were utilized. Objective. The aim of the study was to evaluate the association between dyspepsia and the positivity of H. pylori stool antigen test, to compare this test with serological IgG test. Methods. 125 adult patients were randomly selected from gastroenterology units of Mediterranean and Tajurah clinics in Tripoli. Stool samples were taken for detection of H. pylori antigen by enzyme immunoassay. Blood samples for detection of anti-H. pylori IgG antibodies were taken. Data were statistically analyzed using SPSS. Results. 125 dyspeptic patients: 47 male and 78 female, aged 18-83 years old were examined. 80 patients were infected by H. pylori that was proved by a positive stool test, 88 had a positive IgG test. The prevalence was higher in the patients aged 28-47 years old. There was substantial relation to age, marital status and economic risk factors; there was no association between H. pylori and gender, sources of drinking water, living standards, smoking, family history of peptic ulcer, drug consumption, and blood groups. Conclusions. Relatively high rates of detection by HpSA prove that stool testing might be a reliable, simple, inexpensive, and non-invasive alternative test ащк detectшщт of H. pylori, diagnosing active infection and confirming cure. However IgG test has a low sensitivity, specificity, and accuracy compare to the HpSA test. Thus it can be used for screening purposes.